The Influence of Leadership Style, Work Motivation, and Work Discipline on The Performance of Social Service Employees in Labuhanbatu - Yulia Purnama Sari Ritonga; Yuniman Zebua; Reni Kartikaningsih (Quantitative Economics and Management Studies, 2022)
Human resource management is a process consisting of planning, organizing, leading and controlling activities related to job analysis, job evaluation, procurement, development, compensation, promotion and termination of employment in order to achieve the stated goals. The purpose of this study was to determine the effect of leadership style, work motivation, and work discipline on the performance of the Labuhanbatu District Social Service employees. The data analysis technique in this study used multiple linear regression analysis, with a sample of 31 employees. And the results of the study indicate that leadership style, work motivatio,n and work discipline have a significant effect on employee performance